의과대학의 기능과 동선에 관한 건축계획 연구 - 최광석; 권순정 (의료·복지 건축, 2021)
Purpose: This study is to present basic data on the Architectural planning of the college of medicine by arranging the functional zoning planning, functional unit planning, and circulation planning, based on the diversification of medical education and the changes of Learning spaces. Methods: This study was conducted by literature review on existing medical education method and learning space planning. And then on-site surveys and questionnaire were conducted on existing facilities. Results: The diversification of medical education has already been progressing for a long time, and the development of information technology is integrated into the learning space, and the evolution of the learning method and the flexibility of the learning space give effect to the change of the learning space. ① This study reconstructed the existing classification method of university facilities into the fuctional zoning method that combines the architectural concept of function and movement. ② The functions and functional units of the college of medicine according to the proposed functional zone were arranged, and the space required for the medical college was suggested. ③ The function and type of movement of medical college can be classified into professor/student fusion type, teaching and research separation type, and learning and learning shared space integrated arrangement type. In the future, it is necessary to consider fusion type or integrated arrangement type rather than separation type. Implications: the evolution of the learning method and the flexibility of the learning space give effect to the change of the learning space.
Keywords: College of Medicine; Changes in Medical Education and Learning Space; Composition of Function and Circulation; 의과대학; 의학교육과 학습공간의 변화; 기능 및 동선구성